Antibiotic sensitivity pattern of bacterial isolates and physico-chemical composition of maize flour sold in major markets in Benin City, Midwestern Nigeria - IMARHIAGBE, Emmanuel Esosa; OBAYAGBONA, Omoregbe Nosa; OSARENOTOR, Osayomwanbo; EGHOMWANRE, Aimuanmwosa Frank (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Samples of maize flour sold in selected markets in Benin City, Midwestern Nigeria were evaluated for antibiotic sensitivity pattern, bacteriological and physico-chemical qualities. The adoption of pour plate technique revealed a relatively high bacterial count in order of 10 - 103. Nil Salmonella counts were recorded in this study. Bacillus spp. was the most predominant (41.6 %) and the least predominant among the bacterial isolates was Pseudomonas aeruginosa (7.9 %). The various isolated bacteria showed variable patterns to the evaluated antibiotics, with zones of inhibition ranging from 0 mm to 20 mm. pH value ranged from 6.3 to 6.5; percentage moisture content ranged from 11.87% to 12.31%. There was a slight variation in the titratable acidity of the samples (2.10 to 2.56). Percentage fat content ranged from 5.10 % to 5.32 %, while the percentage protein and ash contents had a range of 8.45 % to 9.0 % and 0.85 % to 1.28 % respectively. This study revealed that maize flour from Benin metropolis markets harbored high bacterial counts with an array of antibiotic resistant bacteria. From a public health point of view, the bacterial quality of this relish food item sold in Benin City markets is indeed alarming and as such stringent measures should be adopted to manage the quality and curtail its possible role increasing the incidence of antibiotic resistance among population. However, this flour type was also observed to possess good basic dietary nutritional requirement (pH, moisture content, protein, fat and ash).